PELAKSANAAN PEMBELAJARAN BAHASA INGGRIS BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS BERDASARKAN KURIKULUM 2013 DI SMP - Mei Kurniawati, Rini (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The research purpose was to describe the planning, implementation, and evaluation of learning, and the problem and solution in implementing learning English to special need learners based curriculum 2013 in SMP Negeri 2 Candi. This research used descriptive qualitative approach. The data collection technique was through interview, observation, and documentation. The test of data validation used triangulation. The data was analyzed through reduction data, display data, and conclusion drawing / verification. The research result indicated that 1) in planning, implementation, and evaluation of learning English to special need learners there were process and evaluation adjustment in the form of re-conveying material and adjustment in giving assignment suitable with the ability of special need learners, 2) the problem faced involved RPP arrangement in which required adjustment in basic competence, indicator, and learning material; the application of scientific approach where the obstruction belonged caused the special need learners could not follow the process well; 3) the solution done was by engaging the teachers in workshop/ training about inclusive education, and there was accompaniment by special assistant teacher who was scheduled well in learning process of special need learners   Keywords: Learning English, Curriculum 2013, Special Need Learners, Inclusive School